HBOC Attenuates Intense Exercise-Induced Cardiac Dysfunction - Li, T.; Zhu, D.; Zhou, R.; Wu, W.; Li, Q.; Liu, J. (International Journal of Sports Medicine, 2012)
The purpose of this study was to investigate whether hemoglobin-based oxygen carrier (HBOC) could protect the heart from intense exercise-induced myocardial dysfunction. Adult male Sprague-Dawley rats were subjected to 5-h intense prolonged running on treadmill with or without HBOC pre-treatment. Immediately after exercise, the heart rate (HR) and oxygen delivery capacity of the blood were measured. After 1 h of rest, echocardiography was performed to assess the post-exercise cardiac function. Then all the hearts were isolated and perfused using the Langendorff model for 1 h. Our results proved that pronged exercise caused significant LV dysfunction, while HBOC pre-treatment attenuated such a damage, as evidenced by the increased oxygen delivery, cardiac fractional shortening (FS), rate-pressure product (RPP), ±dp/dt and coronary flow rate (CF) and decreased myocardial necrosis. The releases of cardiac enzymes, including creatine kinase-MB (CK-MB) and cardiac troponin-I (cTnI) were markedly reduced. No significant difference of cardiac infarct size was observed among groups. In addition, HBOC significantly elevated superoxide dismutase (SOD) activity and decreased hydrogen peroxide (H2O2) formation, which indicated the exercise-induced cardiac oxidative damage was inhibited. In conclusion, HBOC pre-treatment showed a promising cardioprotective effect on prolonged exercise-induced cardiac dysfunction, which was probably associated with its ability to decrease myocardium oxidative stress.
Keywords: hemoglobin-based oxygen carrier; exercise; echocardiography; myocardium; oxidative stress